Bancassurance – one of the most important distribution channels in Europe - Elda MARZAI (ABLIZ) (Theoretical and Applied Economics, 2018)

(untitled)
During the financial crisis, most of the financial institutions are trying to improve new products and services for generate new revenues. So, the implementation of bancassurance activity in the banking field contributes to strengthening of the competitive environment, developing new products in insurance and satisfying the customers’ needs in one financial institution. This paper aims to highlight different perspectives about bancassurance concept, history and development in this period full of changes and the identification of main strengths, weaknesses, opportunities and threats which contributing to the sustainability of bancassurance. In addition, will be presented a situation regarding bancassurance development in Romania.